Myocarditis in COVID-19 Patients: A Cross-Sectional Study - Lahraoui, Myriam; Elghali, Tanae; Lahlou, Laila; Doghmi, Nawal; Cherti, Mohamed (Cardiology and Cardiovascular Medicine, 2023)
Myocarditis is an inflammatory disease of the myocardium, the clinical presentation can vary from an asymptomatic form to dilated cardiomyopathy and heart failure that can be fatal. The gold standard for diagnosis is endomyocardial biopsy, but this is rarely used, leaving for cardiac MRI a wider indication. All this explains the diagnostic difficulty, which is based on a number of arguments. Myocarditis is due to infectious etiologies, essentially viral, but also autoimmune and toxic causes. The SARS-CoV-2 declared responsible for a pandemic in March 2020 is one of the viruses recently implicated in the occurrence of myocarditis. Our study gathered 116 covid-positive patients in order to describe the population having developed myocarditis and to compare these characteristics to the general population.